2015
DOI: 10.1096/fj.15-270256
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB‐repressing factor phosphorylation regulates transcription elongation via its interactions with 5'→3' exoribonuclease 2 and negative elongation factor

Abstract: NF-κB-repressing factor (NKRF) inhibits transcription elongation by binding to specific sequences in target promoters. Stimuli such as IL-1 have been shown to overcome this inhibitory action and enable the resumption of transcription elongation machinery by an unknown mechanism. Using mass spectrometry and in vitro phosphorylation analyses, we demonstrate that NKRF is phosphorylated within 3 different domains in unstimulated HeLa cells. Phosphoamino acid mapping and mutation analysis of NKRF further suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Interestingly, we observe, however, that the DUF3469 domain of NKRF is not essential for binding of XRN2. Consistent with this, an independent study recently reported that a region downstream of the DUF3469 is important for the interaction between NKRF and XRN2 (77). Our results therefore suggest that although the DUF3469 domain of NKRF may form contacts with XRN2, the nature of the XRN2-NKRF and XRN2-CARF interactions might differ, with other regions of NKRF likely contributing to its association with XRN2.…”
Section: Discussionsupporting
confidence: 60%
“…Interestingly, we observe, however, that the DUF3469 domain of NKRF is not essential for binding of XRN2. Consistent with this, an independent study recently reported that a region downstream of the DUF3469 is important for the interaction between NKRF and XRN2 (77). Our results therefore suggest that although the DUF3469 domain of NKRF may form contacts with XRN2, the nature of the XRN2-NKRF and XRN2-CARF interactions might differ, with other regions of NKRF likely contributing to its association with XRN2.…”
Section: Discussionsupporting
confidence: 60%
“…In agreement with others, we find that NKRF interacts with XRN2 ( Figure 3A) [8,9,29]. However, we also show that efficient binding of NKRF to XRN2 absolutely depends on the integrity of the XTBD ( Figure 5A).…”
Section: Part 1 Ofsupporting
confidence: 92%
“…Experiments on human U-2 OS osteosarcoma cell lines rovide circumstantial evidence for the latter, as XRN2 immunofluorescence staining is observed in both nucleus and nucleoplasms, whereas NKRF locates to the nucleolus, from which the nucleoplasmic CDKN2AIP appears excluded42. As the phosphorylation status of NKRF may modulate the interaction between NKRF and XRN2 43, it will be interesting to see whether it also affects localization of NKRF and/or XRN2.…”
Section: Resultsmentioning
confidence: 99%